1996
DOI: 10.1136/bjsm.30.4.324
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of injuries and other health problems in the Auckland Citibank marathon, 1993.

Abstract: Objective-To describe the incidence of injuries and other health problems sustained during participation in a marathon. Methods-A cohort study was undertaken involving the 1993 Auckland Citibank marathon participants. Demographic data and information on injuries and other health problems sustained during, immediately after, and 7 d following the marathon were obtained from a pre-race questionnaire, the medical aid posts, and a post-race questionnaire. Results-Of the 1219 starters, 916 (75.1%) completed both qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 4 publications
1
31
0
3
Order By: Relevance
“…Further details on the types of problems sustained have been reported previously. 7 Decreased risks of constitutional problems were associated with increasing age, with significant decreases in risk observed for those aged 35-39 (OR 0.43; 95% CI 0.21 to 0.87) and for those aged 40 or older (OR 0.43; 95% CI 0.22 to 0.85) compared with those aged less than 25. Increased risks were associated with being unwell in the previous two weeks (OR 1.74; 95% CI 1.19 to 2.56) (table 1).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Further details on the types of problems sustained have been reported previously. 7 Decreased risks of constitutional problems were associated with increasing age, with significant decreases in risk observed for those aged 35-39 (OR 0.43; 95% CI 0.21 to 0.87) and for those aged 40 or older (OR 0.43; 95% CI 0.22 to 0.85) compared with those aged less than 25. Increased risks were associated with being unwell in the previous two weeks (OR 1.74; 95% CI 1.19 to 2.56) (table 1).…”
Section: Resultsmentioning
confidence: 96%
“…Further details on the types of problems sustained have been reported previously. 7 StiVness or pain, or both, in the front thigh was reported by 526 (60.1%) subjects and was shown to be positively associated with participation in cycling, increased number of days for each week of training, and with drinking alcohol once a month or more (table 3). An inverted-U relation was found between age and risk of hamstring injury, with increased risks only in those aged 30-34 (OR 1.83, 95% CI 1.04 to 3.22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen prospective cohort studies [9][10][11][12][13][14][15][16][17][18][19][20][21] and four retrospective cohort studies [22][23][24][25] were included. The study characteristics of the selected studies were described to obtain insight into the homogeneity of the study populations (table 1).…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…With such a large number of people running, the risk and incidence of running-related injuries will likely continue. During a 12-month period of running, it has been reported that up to 90% of runners will suffer a running-related injury (Fields, Sykes, Walker, & Jackson, 2010;Satterthwaite, Larmer, Gardiner, & Norton, 1996;Van Gent, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%